PENYULUHAN TENTANG KHASIAT TANAMAN DAUN AFRIKA DAN DAUN KELAPA SAWIT UNTUK PENYEMBUHAN PENYAKIT KOLESTEROL DI PUSKESMAS PATUMBAK - Evi Deviana Gultom; Angga Nugraha Sanjaya (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Counseling on the efficacy of African leaf plants and oil palm leaves which aims to provide benefits on cholesterol healing in health centers in Patumbak district aimed at the elderly, by applying promotive and preventive nature through planning, mobilization, implementation, monitoring, control and assessment. Counseling on the efficacy of African leaf plants and oil palm leaves at the Patumbak Public Health Center, Deli Serdang Regency is aimed at increasing the understanding of the elderly to identify symptoms of high cholesterol or not, so that they can prevent or treat them, and the elderly can know the importance of checking cholesterol levels. Counseling will be carried out in a lecture style with conditions with discussion and brain storming that stimulates the counseling atmosphere. The evaluation of activities was assessed from the support of the Patumbak Health Center, the timeliness of implementation, the facilities used, the number of participants who took part in the counseling and the participation of the participants. Counseling participants were invited to express opinions, especially the problems faced at the Patumbak Health Center regarding cholesterol so that solutions could be found together. The results obtained The elderly after receiving counseling can understand well the benefits of counseling from the Patumbak Public Health Center regarding the use of the efficacy of African leaf plants and oil palm leaves for healing. The elderly families lack knowledge about the importance of health for the elderly. The family is willing to provide education and enthusiasm about the importance of utilizing the benefits of African leaf plants and oil palm leaves. The elderly after receiving counseling can understand well the benefits of counseling from the Patumbak Public Health Center regarding the use of the efficacy of African leaf plants and oil palm leaves for treating cholesterol in the elderly. However, after attending the counseling, these elderly people can understand more fully the benefits of counseling. Community Health Center cadres who have been providing services to the elderly to a minimum, can change well by providing innovative promotions.